Molecular Cloning, Expression and Purification of Protein TB10.4 Secreted by Mycobacterium Tuberculosis - Aida Gholoobi; Mojtaba Sankian; Reza Zarif; Zahra Farshadzadeh; Forugh Youssefi (Iranian Journal of Basic Medical Sciences, 2010)
Objective(s)Tuberculosis (TB) is the leading cause of mortality among the infectious diseases, especially in developing countries. One of the main goals in tuberculosis research is to identify antigens which have the ability of inducing cellular and/or humoral immunity in order to use them in diagnostic reagents or vaccine design. The aim of this study was to clone and express the TB10.4 protein in Escherichia coli expression system.Materials and MethodsDNA was extracted from Mycobacterium tuberculosis H37Rv. Gene specific primers were designed using Gene Runner software according to sanger sequence database. Gene tb10.4 fragment was amplified by PCR method and purified tb10.4 gene was cloned into pET 102/D vector. Plasmid containing pET102/D-10.4 was transformed into competence E. coli TOP10. A positive transformant was chosen and plasmids DNA was isolated and subsequently transformed into competence E. coli BL21(DE3). The bacterium was induced by IPTG and its lysates were loaded directly onto SDS-PAGE. Purified recombinant protein was achieved using metal affinity chromatography (Ni-nitrilotriacetic acid).ResultsTB10.4 molecule was successfully cloned, expressed, and purified. An approximately 26.4 kDa exogenous protein was observed on the SDS-PAGE. The recombinant protein was confirmed by DNA sequencing of correct insert.ConclusionThe success of expressing the TB10.4 protein could serve as a basis for further studies on the usefulness of the gene and its expression product in the development of subunit vaccine and diagnostic method.